Effects of Periodic Intensive Insulin Therapy: An Updated Review - Shu Dong, FNP; Hien Lau, BSc; Cody Chavarria, BSc; Michael Alexander, MSc; Allison Cimler, FNP; John P. Elliott, MD; Sandra Escovar, MD; Jack Lewin, MD; James Novak, MD; Jonathan R.T. Lakey, PhD, MSM (Elsevier, 2019)
ABSTRACT: Background: Traditional insulin treatment for diabetes mellitus with insulin administered subcutaneously yields nonpulsatile plasma insulin concentrations that represent a fraction of normal portal vein levels. Oral hypoglycemic medications result in the same lack of pulsatile insulin response to blood glucose levels. Intensive treatments of significant complications of diabetes are not recommended due to complicated multidrug regimens, significant weight gain, and the high risk of hypoglycemic complications. Consequently, advanced complications of diabetes do not have an effective treatment option because conventional therapy is not sufficient. Intensive insulin therapy (IIT) simulates normal pancreatic function by closely matching the periodicity and amplitude of insulin secretion in healthy subjects; however, the mechanisms involved with the observed improvement are not clearly understood. Objective: The current review aims to analyze the pathophysiology of insulin secretion, discuss current therapies for the management of diabetes, provides an updates on the recent advancements of IIT, and proposes its mechanism of action. Methods: A literature search on PubMed, MEDLINE, Embase, and CrossRef databases was performed on multiple key words regarding the history and current variations of pulsatile and IIT for diabetes treatment. Articles reporting the physiology of insulin secretion, advantages of pulsatile insulin delivery in patients with diabetes patients, efficacy and adverse effects of current conventional insulin therapies for the management of diabetes, benefits and shortcomings of pancreas and islet transplantation, or clinical trials on patients with diabetes treated with pulsed insulin therapy or advanced IIT were included for a qualitative analysis and categorized into the following topics: mechanism of insulin secretion in normal subjects and patients with diabetes and current therapies for the management of diabetes, including oral hypoglycemic agents, insulin therapy, pancreas and islet transplantation, pulsed insulin therapy, and advances in IIT. Results: Our review of the literature shows that IIT improves the resolution of diabetic ulcers, neuropathy, and nephropathy, and reduces emergency room visits. The likely mechanism responsible for this improvement is increased insulin sensitivity from adipocytes, as well as increased insulin receptor expression. Conclusions: Recent advancements show that IIT is an effective option for both type 1 diabetes mellitus and type 2 diabetes mellitus patient populations. This treatment resembles normal pancreatic function so closely that it has significantly reduced the effects of relatively common complications of diabetes in comparison to standard treatments. Thus, this new treatment is a promising advancement in the management of diabetes. (Curr Ther Res Clin Exp. 2019; 80:XXX-XXX). Keywords: Diabetes, Complications, Infusion, Insulin, Intravenous